Recent Progress on Engineering Highly Efficient Porous Semiconductor Photocatalysts Derived from Metal–Organic Frameworks - Zhan, Wenwen; Sun, Liming; Han, Xiguang (Nano-Micro Letters, 2019)
Porous structures offer highly accessible surfaces and rich pores, which facilitate the exposure of numerous active sites for photocatalytic reactions, leading to excellent performances. Recently, metal–organic frameworks (MOFs) have been considered ideal precursors for well-designed semiconductors with porous structures and/or heterostructures, which have shown enhanced photocatalytic activities. In this review, we summarize the recent development of porous structures, such as metal oxides and metal sulfides, and their heterostructures, derived from MOF-based materials as catalysts for various light-driven energy-/environment-related reactions, including water splitting, CO2 reduction, organic redox reaction, and pollution degradation. A summary and outlook section is also included. Highlights: 1 In this review, we survey the recent developments in the fabrication of metal–organic framework (MOF)-derived porous semiconductor photocatalysts toward four kinds of energy-/environment-related reactions. 2 A comprehensive summary of highly efficient MOF-derived photocatalysts, particularly porous metal oxides and metal sulfides, and their heterostructures are provided. 3 Enhanced photocatalytic performance achieved with MOF-derived porous heterostructures as the photocatalyst is discussed in detail.